STUDENTS’ DIFFICULTIES IN WRITING PROCEDURE TEXT - Ningsih, Rahayu Wulan; M. Said, Mawardin; Anggreni, Afrillia; Hastini, Hastini (e-Journal of ELTS (English Language Teaching Society), 2025)
This research aimed to discover students’ dfficulties in writing procedure text. qualitative descriptve design was used. The subject of this research was 7 students in ninth grade at SMP Negeri Poso Pesisir. The instrument of this research was documents of the result of the students’ writing that given by the English teacher. Based on the data analysis, the data showed that the students have difficulties in writing procedure text, especially in term on of generic stucture: Goal, material/ingredients, step. And in language features: the use of adverbial of sequence/temporal conjunction, use of imperative sentence, use of adverbials, use of action verb, and use of present tense. Based on the difficulties the teachers are expected to be facilitator for students in learning writing procedure text and for students they expected to have motivation in learning especially in writing generic structure and language features.